A standing pararectal approach to treat small colon obstruction by a pedunculated lipoma. (8th February 2018) - Durket, E.; Albanese, V.; Steward, S. K.; Freeman, D. E.
Summary: In an 18‐year‐old Paso Fino mare presented with mild colic of 36 h duration, a luminal obstruction was found on rectal palpation in the most oral part of the rectum, and this appeared to be caused by a tight band on the left side. A standing procedure was used that involved pararectal dissection with long‐handled instruments to the level of the constricting band, guided by a hand in the rectum. A hooked bistoury designed for treating entrapped epiglottis was used to transect the band, which immediately released the obstruction and allowed manual evacuation of the aboral end of the small colon. The band was most likely the pedicle of a pedunculated lipoma that had encircled the oral end of the rectum. The mare made a complete recovery.